2014
DOI: 10.1155/2014/517504
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms Involved in Folate Metabolism and Maternal Risk for Down Syndrome: A Meta-Analysis

Abstract: Inconclusive results of the association between genetic polymorphisms involved in folate metabolism and maternal risk for Down syndrome (DS) have been reported. Therefore, this meta-analysis was conducted. We searched electronic databases through May, 2014, for eligible studies. Pooled odds ratios with 95% confidence intervals were used to assess the strength of the association, which was estimated by fixed or random effects models. Heterogeneity among studies was evaluated using Q-test and I 2 statistic. Subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Furthermore, when Caucasian samples were stratified by geographic and demographic criteria the estimates revealed that the risk is higher in those of nonresidential European descent (OR = 1.47; 95% CI = 1.02-2.11; dominant model) than in residential European Caucasians (OR = 1.31; 95% CI = 1.01-1.70; dominant model). On contrary, when the study was conducted on the Caucasian from Mediterranean regions no significant association was observed (OR = 1.19; 95% CI = 0.91-1.55; dominant model), which suggests that the manifestation of the effect of MTRR rs1801394 66A > G is also dependent on geographic and dietary factors [33].…”
Section: Methionine Synthase and Methionine Synthase Reductase (Mtr Amentioning
confidence: 83%
See 3 more Smart Citations
“…Furthermore, when Caucasian samples were stratified by geographic and demographic criteria the estimates revealed that the risk is higher in those of nonresidential European descent (OR = 1.47; 95% CI = 1.02-2.11; dominant model) than in residential European Caucasians (OR = 1.31; 95% CI = 1.01-1.70; dominant model). On contrary, when the study was conducted on the Caucasian from Mediterranean regions no significant association was observed (OR = 1.19; 95% CI = 0.91-1.55; dominant model), which suggests that the manifestation of the effect of MTRR rs1801394 66A > G is also dependent on geographic and dietary factors [33].…”
Section: Methionine Synthase and Methionine Synthase Reductase (Mtr Amentioning
confidence: 83%
“…Nevertheless, the meta-analysis conducted in 2009 on 623 DS bearing and 936 control mothers [31], confirmed association of this polymorphism in maternal genome with the elevated risk of having DS baby. Further analyses with stratified data, performed in recent time [32,33], suggest a significant effect in Caucasians under both dominant and recessive genetic models. The estimated score for minor Allele "G" among Caucasian women was 35.8-54.3%, among Brazilian women was from 40.0 to 48.0% and among Asian mothers was from 41.5 to 62.5% [32][33][34].…”
Section: Methionine Synthase and Methionine Synthase Reductase (Mtr Amentioning
confidence: 95%
See 2 more Smart Citations
“…There is some heterogeneity in these data as studies have inconsistently reported the association of specific effect alleles (or underlying polymorphisms), so additional work is necessary to clarify the risk variants and their effect size. More recently, meta-analyses have identified associations between MTHFD1 polymorphisms, such as the MTHFD1 G1958A variant, as being associated with increased risk for birth defects [16], [17], [18]. Additionally, two missense mutations, rs7946 and rs897453, in PEMT , an enzyme required for de novo production of choline, have been associated with altered homocysteine levels and neural tube defects, respectively [19, 20].…”
Section: Genetic Polymorphism Dietary Choline and Pregnancy Outcomesmentioning
confidence: 99%